2022
DOI: 10.3389/fpsyg.2022.851332
|View full text |Cite
|
Sign up to set email alerts
|

How Social Support Impact Teachers’ Mental Health Literacy: A Chain Mediation Model

Abstract: Teachers have an important social role, and their mental health literacy is very important to their own abilities as educators and to the growth and development of those they educate. This study explored the mechanism underlying the influence of social support on teachers’ mental health literacy by conducting a questionnaire survey of 573 teachers. The results showed that social support can influence teachers’ mental health literacy not only through the separate effects of life satisfaction and coping tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…We found a positive correlation between mental health literacy and positive coping and a negative correlation between mental health literacy and negative coping. This is similar to the results in a sample of teachers [ 43 ]. A high level of mental health literacy represents more knowledge and beliefs about identifying risk factors, managing pressure, and seeking appropriate help [25].…”
Section: Discussionsupporting
confidence: 91%
“…We found a positive correlation between mental health literacy and positive coping and a negative correlation between mental health literacy and negative coping. This is similar to the results in a sample of teachers [ 43 ]. A high level of mental health literacy represents more knowledge and beliefs about identifying risk factors, managing pressure, and seeking appropriate help [25].…”
Section: Discussionsupporting
confidence: 91%
“…To assess potential multicollinearity among the predictors, the variance inflation factors (VIF) were estimated. Our analysis indicated that the VIF indices for predictors were 1.37 or below, indicating no serious multicollinearity ( Li et al, 2022 ).…”
Section: Methodsmentioning
confidence: 82%
“…instructional strategies, classroom management & student engagement). A survey study conducted in China on teachers found that Social Support has a significantly positive relationship with teachers' mental health literacy, coping tendencies, and life satisfaction (Li et al, 2022). Support from social factors increases the self-efficacy of teachers.…”
Section: Literature Reviewmentioning
confidence: 99%